Attitudes toward AI in Writing: Opportunities and Challenges for English Students’ Writing Skills - Dony Efriza; Affan Yusra; Heri Usmanto; Rully Andi Yaksa (ENGLISH FRANCA : Academic Journal of English Language and Education, 2026)
The objective of this study was to examine the influence of learning and innovation skills on students’ attitudes toward the use of artificial intelligence (AI) in writing and its effect on their writing proficiency. A sequential explanatory mixed-method design was employed to provide both statistical and in-depth insights. The quantitative data were gathered by means of questionnaire and writing assessment from 34 second semester English Department students of the Faculty of Teacher Training and Education, Universitas Jambi through stratified random sampling from the population of 120 students. The questionnaire measured students’ attitudes towards AI in writing through communicative, behavioural, and cognitive indicators and the IELTS writing rubric was used to assess writing proficiency. To understand the experiences and perceptions of AI tools such as ChatGPT and Grammarly, qualitative data was collected through semi-structured interviews and classroom observations of seven purposively selected participants. The results showed that students’ attitude towards AI significantly affected their writing skills (Sig. = 0.006 < 0.05). Students who had positive and critical attitudes towards AI produced more coherent, original and well-organized writing, whereas students who were overly dependent on AI performed worse and showed lower creativity. The study finds standard artificial intelligence can be an effective assistive device in developing writing ability when it is paired with sufficient cognitive and ethical consciousness. These findings underline the significance of advocating digital literacy as a norm, critical thinking, and responsible utilization of AI in English language education.